Temporal trends in anthropogenic marine macro-debris and micro-debris accumulation on the California Channel Islands - Steele, Clare L. W.; Miller, Michaela R. (Frontiers in Marine Science, 2022)
Accumulation of anthropogenic marine debris on shorelines is an issue of global concern, even impacting areas that are remote, uninhabited, or have protected area status. On islands in Southern California, USA, within the boundaries of a National Park and National Marine Sanctuary, we collected macro-debris on beaches and assessed micro-debris in beach sediment seasonally between 2016-2020. Macro-debris (>5mm) was collected from seven beaches on two California Channel Islands and two sites on the mainland. We assessed both the number of items collected and total mass of debris. Composition of macro-debris items was dominated by plastics, particularly fragmented hard and foamed plastics and food packaging. A substantial quantity of lost or discarded fishing gear was collected, with the most fishery-related debris found at sites with historically highest spiny lobster fishing effort. The initial density of debris items ranged from 0.01-0.13 items m-2 and the initial density of debris mass ranged from 0.01-0.02 kg m-2. Mean accumulation rates of debris were strongly site-dependent and ranged from 0.03-0.34 items m-2 yr-1 and 0.01-0.05 kg m-2 yr-1, and tended to be highest in the fall and winter months. Anthropogenic micro-debris (<5mm) was found in beach sediment at all sites. Micro-debris had no statistically significant relationship with accumulation rates of total macro-debris items, or plastic macro-debris items. There were, however, statistically significant relationships between accumulation rates of total macro-debris mass and plastic macro-debris mass. We compared the rate of accumulation of fishing debris items and mass during the lobster season (October-March) for the years 2017 to 2020. The accumulation of fishery-related debris differed significantly among sites, with apparent declines over time, likely reflecting declining effort in the fishery and trap-limit regulations implemented in the 2017-2018 season. Our assessment of marine debris accumulation on California Channel Island beaches has provided detailed information on the types of debris and patterns of accumulation. Unfortunately, remoteness from direct human impact and protected-area status does not protect these habitats against the onslaught of marine litter. Assessments of marine debris are critical to identify sources, to inform policy and to support efforts to reduce the impact of marine litter on vital coastal ecosystems.